Non-verbal predications in Zarma - Abdoulaye, Mahamane L.; Abdoulrazikou, Salimata (Linguistik Online, 2024)
This article presents new findings in the use of copulas nôo ‘be’ and ti ‘be’ in non-verbal predications in Zarma (Songhay; Niger, Nigeria). Based on some exclusive contexts of use and some morphosyntactic criteria, the article distinguishes a basic type of predication with one term “NP + nôo” used in deictic identification (e. g.: Abdù nôo ‘it’s Abdu’) and a type of predication with two terms “NP1 + NP2 + nôo” used in nominal predications and equative sentences (e. g.: wodìn Abdù nôo ‘that is Abdu’). The article shows that copula ti replaces copula nôo in negation but also in non-verbal focus constructions where it is generally preceded by the subordinating conjunction kà/gà and very likely marks the presupposed part of the sentence (e. g.: [Muusà nôo] kà ti càwkŏo ‘[it’s Musa] who is a student’). Finally, the article shows that in Zarma, it is the one-term predication “NP + nôo” that is recruited to mark focus-fronted constituents of verbal and non-verbal predications, thus confirming an observation already made about other languages.